Short‐term complications and post‐acute sequelae in hospitalized paediatric patients with COVID‐19 and obesity: A multicenter cohort study. Issue 2 (12th October 2022) - Valenzuela, Gonzalo; Alarcón‐Andrade, Gonzalo; Schulze‐Schiapacasse, Clara; Rodríguez, Rocío; García‐Salum, Tamara; Pardo‐Roa, Catalina; Levican, Jorge; Serrano, Eileen; Avendaño, María José; Gutiérrez, Monserrat; Godoy, Loreto; Céspedes, Pamela; et al.
Summary: Background: Obesity increases the severity of coronavirus disease 2019 illness in adults. The role of obesity in short‐term complications and post‐acute sequelae in children is not well defined. Objective: To evaluate the relationship between obesity and short‐term complications and post‐acute sequelae of SARS‐CoV‐2 infection in hospitalized paediatric patients. Methods: An observational study was conducted in three tertiary hospitals, including paediatric hospitalized patients with a confirmatory SARS‐CoV‐2 RT‐PCR from March 2020 to December 2021. Obesity was defined according to WHO 2006 (0–2 years) and CDC 2000 (2–20 years) growth references. Short‐term outcomes were intensive care unit admission, ventilatory support, superinfections, acute kidney injury, and mortality. Neurological, respiratory, and cardiological symptoms and/or delayed or long‐term complications beyond 4 weeks from the onset of symptoms were considered as post‐acute sequalae. Adjusted linear, logistic regression and generalized estimating equations models were performed. Results: A total of 216 individuals were included, and 67 (31.02%) of them had obesity. Obesity was associated with intensive care unit admission (aOR = 5.63, CI95% 2.90–10.94), oxygen requirement (aOR = 2.77, CI95% 1.36–5.63), non‐invasive ventilatory support (aOR = 6.81, CI95% 2.11–22.04), overall superinfections (aOR = 3.02 CI95% 1.45–6.31), and suspected bacterial pneumonia (aOR = 3.00 CI95% 1.44–6.23). For post‐acute sequalae, obesity was associated with dyspnea (aOR = 9.91 CI95% 1.92–51.10) and muscle weakness (aOR = 20.04 CI95% 2.50–160.65). Conclusions: In paediatric hospitalized patients with COVID‐19, severe short‐term outcomes and post‐acute sequelae are associated with obesity. Recognizing obesity as a key comorbidity is essential to develop targeted strategies for prevention of COVID‐19 complications in children.